Репресії селян на Миколаївщині під час Голодомору 1932—1933 рр.: за матеріалами кримінальних справ - Зеркаль, М. (Краєзнавство, 2018)
Автором досліджується один з аспектів втілення політики геноциду українського народу комуністичного тоталітарного режиму за матеріалами кримінальних справ які обґрунтовували застосування кримінальних покарань до значної маси сільського населення в 1932–1933 роках. Дана проблема висвітлена в контексті політики геноциду українського народу державними правоохоронними органами. Здійснюється спроба привернути увагу читачів не просто до статистики жертв, а на підставі усної історії задокументованої мовою протоколів дослідити зламані життя конкретних людей як представників значної маси аналогічних злочинних діянь репресивних правоохоронних органів. Еxplores another embodiment the direction of the Ukrainian people genocide by the communist totalitarian regime on the basis of criminal cases that justify the use of criminal penalties to the mass of the rural population in 1932–1933. Despite the ruling hunger Soviet state machinery continued their work even attempts to suppress discontent exercised identify policy of genocide. People tried desperately to win their right to life, but the environment of fear and horror, the transformation of the psyche under the influence of hunger ensure domination of the Soviet system. Finally, it is not clear that the reasoning advocated argument in the minds of perpetrators of criminal orders, because everyone understood and saw that all the perpetrators sooner or later may expect the fate of prisoners. Unfortunately, we have witnessed such a shameful phenomenon as accusations of his fellow villagers for the sake of confiscated. Some Ukrainian certify lie to others. In politics famine Soviet system applied also open the repressive policy of the Ukrainian population. So far in 2008 documented Mykolayiv citizens who are in the grip of terror, preserved their criminal cases. Exploring the tragic events 1932–1933 rokiv impressive scale loss of life, and for each figure is an individual, his life, hope, frustration and terrible tragedy of death. The final amount of losses and to this day remains controversial. Our society should not just remember and carefully examine, monitor, synthesize contemporary demographic processes in Ukrainian society. Always mindful of 3.5 to 9 million murdered within two years of the Soviet totalitarian system should also analyze the statistics of population today, for example, only nine months of 2016 only in Mykolaiv oblast population decreased by 5.3 thousands of people and without introducing policies terrible famine without workers is only for this period Mykolayiv population decreased by 2.3 countryside. This issue is covered in the context of ethnic genocide of the Ukrainian people and the state party by law enforcement agencies. Автором исследуется ещё одно направление реализации политики геноцида украинского народа со стороны коммунистического тоталитарного режима на основании уголовных дел которые применяли нормы уголовного права к массе сельского населения на Николаевщине в 1932–1933 гг. Данная проблема освещается в контексте политики этнического геноцида украинского народа государственными партийными и правоохранительными органами.